Electrochemical quartz crystal microbalance study of electrodeposition of copper-selenium thin films - Dang, Thi Bich Hop (H. : ĐHQGHN, 2017)
The deposition of Copper-Selenium thin films was studied by using a combination of Cyclic Voltammetry (CV) and Electrochemical Quartz Crystal Microbalance (EQCM). The values of the equivalent atomic mass (M/z) grown at the gold EQCM sensor during electrodeposition at varying potentials and constant potentials were analyzed to understand the mechanism of the growing process. The composition of the films determined by EDS supports the assumption of the deposition process which is based on the EQCM studies. The obtained results indicate the role of sulfamic acid as a comlexing agent. The concentration of 20 mM of sulfamic acid and the growing potential of - 0.9 V were found to be the most suitable conditions for deposition of Copper-Selenium layers towards CIGS thin film solar cell application.